Trends in nursing knowledge production regarding the COVID-19 pandemic in Brazil - Mônica Emanuele Köpsel Fusari; Gustavo Baade de Andrade; Messias Lemos; Caroline Cechinel Peiter; Gabriela Marcellino de Melo Lanzoni; José Luís Guedes dos Santos (Universidade Federal do Ceará, 2024)
Objective: to analyze the investigative trends of theses and dissertations on COVID-19 from graduate programs in Nursing in Brazil. Methods: a bibliometric study conducted using the Theses and Dissertations Catalog from the Coordination for the Improvement of Higher Education Personnel, with bibliometric data analysis through IRAMUTEQ. Results: 82 works were selected, with the majority being dissertations (87.8%). They were distributed into six classes: 1) Nursing professionals' mental health. 2) Pregnant and postpartum women health. 3) Adaptation of care for people in vulnerable situations. 4) Human being and being a nurse: living and facing the virus. 5) Nursing work reorganization, and 6) COVID-19 repercussions for nursing. Conclusion: research is concentrated on nursing working conditions, mental health, and the care workflows reorganization. Contributions to practice: the study brings visibility to the knowledge production in Nursing within the context of the COVID-19 pandemic in Brazil and identifies gaps for future studies.